Landau-Migdal vs. Skyrme - Speth, J.; Krewald, S.; Gru¨mmer, F.; Reinhard, Paul-Gerhard; Lyutorovich, N.; Tselyaev, V. (Nuclear Physics A, 2014)
The magnitude and density-dependence of the non-spin-dependent Landau-Migdal parameters are derived from Skyrme energy functionals and compared with the phenomenological ones. We perform RPA calculations with various approximations for the Landau-Migdal particle-hole interaction and compare them with the results obtained with the full Skyrme interaction. For the first time the next to leading order in the Landau-Migdal approach is considered in nuclear structure calculations.
CRIS-Team Scopus Importer:2023-07-24
Keywords: Landau parameters; Skyrme forces